Vidas construidas : biografías de arquitectos - Zabalbeascoa, Anatxu (Gustavo Gili)
Biografías de: Brunelleschi, Miguel Angel, Palladio, Bernini, Borromini, Wren, Piranesi, Soane, Gaudí, Wright, Mackintosh, Loos, Van Doesburg, Mies van der Rohe, Le Corbusier, Sant'Elia, Aalto, Kahn y Terragni.